2000
DOI: 10.1211/0022357001777379
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions between HIV-1 Protease Inhibitors in Rats: Study on Combinations of Two Kinds of HIV-1 Protease Inhibitors

Abstract: The drug interactions between four human immune deficiency virus (HIV-1) protease inhibitors have been characterized by in-vitro metabolic studies using rat liver microsomal fractions and in-vivo oral administration. In this study, a new HPLC analytical method developed by us was used for the simultaneous determination of saquinavir and nelfinavir in rat plasma and microsomes. The metabolic clearance rates (Vmax/Km) of saquinavir, nelfinavir, and indinavir were 170.9 +/- 10.9, 126.1 +/- 4-4, and 73.0 +/- 2.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 16 publications
(21 reference statements)
3
22
0
Order By: Relevance
“…SQV and NFV exhibited competitive inhibition and no evidence of partial inhibition. The inhibitory potency for the inhibition of 1Ј-OH-midazolam observed in rat microsomes is comparable to results published by Shibata et al (2000).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…SQV and NFV exhibited competitive inhibition and no evidence of partial inhibition. The inhibitory potency for the inhibition of 1Ј-OH-midazolam observed in rat microsomes is comparable to results published by Shibata et al (2000).…”
Section: Discussionsupporting
confidence: 87%
“…For all four compounds, inhibition was clearly evident in the hepatocyte preparations, and this result is consistent with in vivo studies in both humans and rats (Edwards et al, 1988;Olkkola et al, 1993;Davis et al, 1994;Yamaji et al, 1999;Yamano et al, 1999;Shibata et al, 2000). The two protease inhibitors studied, SQV and NFV, were very potent inhibitors of midazolam hydroxylation with K i values Յ1 M. In the case of ENX and CLAR inhibition, K i values were much less potent in the region of 100 M. All compounds are known to be substrates for the solute carrier transporter proteins (Sasabe et al, 1997;Yamano et al, 1999;Su et al, 2004;Maeda et al, 2007;Seithel et al, 2007;Giacomini et al, 2010), thus there was an expectation that hepatocytes would show higher sensitivity to inhibition than microsomes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…31,32) In our previous studies on pharmacokinetic interactions among the HIV PIs currently used in clinical therapy, we observed that IDV inhibited the metabolism of APV, NFV and SQV with K i values of 0.67, 2.76 and 3.55 mM, respectively. [10][11][12][13] After oral administration of APV, SQV or NFV with IDV, their AUC values in the presence of IDV were increased 1.6-, 9.5-and 2.3-fold, respectively, compared with any of them alone. On the other hand, the AUC values of APV, SQV and NFV after intravenous co-administration with IDV increased by 1.4-, 1.2-and 1.5-fold, respectively, and showed no notable increase compared to those obtained from oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] According to the previous studies, the degrees of in vivo pharmacokinetic interaction between any combination of two drugs selected out of the above five were highly variable. [10][11][12] Even though IDV had the strongest inhibitory effect on APV metabolism in rat liver microsomes, the in vivo effects of an HIV PI after co-administration with IDV could not always be predicted from in vitro results, suggesting the presence of another interaction process besides metabolism in the liver. 13) It has been suggested that in some drugs the role of intestinal metabolism is greater than that of hepatic metabolism in the overall first-pass effect.…”
mentioning
confidence: 97%